Analisis Ketahanan (Resilience) Pedagang Kaki Lima di Masa Pandemi Covid-19: Studi Kasus Jalan Sukasari, Kota Bogor, Jawa Barat - Mujio Mujio; Umar Mansyur; Ichwan Arif; Rindiani Agustina Rahayu; Amara Desiana Yura (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2022)
Street vendors are one part of SMEs who have experienced the impact of Covid-19, inclusive of street vendors on Jalan Sukasari, Bogor City. The purpose of this study was to determine the most influential factors in recovery and resilience strategies, as well as street vendors in Sukasari street, Bogor City, and alternative recovery strategies for street vendors on Jalan Sukasari, Bogor City. Data collection was conducted by interviews and questionnaire filler by street vendors in Sukasari street. The research analysis used is the Fuzzy-Eckenrode approach analysis as one approach forMulti-Criteria Decision Making. The most influential factors on the resilience of street vendors in Sukasari street, Bogor city after the Covid-19 pandemic based on Fuzzy-Eckenrode analysis are work culture, leadership, and social networks. Alternative strategies based on Fuzzy-TOPSIS analysis are government assistance strategies, digital technology introduction strategies, and debt relief strategies.